Faktor yang Mempengaruhi Penjualan Toko Kelontong di Kecamatan Sukarame Bandar Lampung - Destia Pentia; Evi Yuniarti (Politeknik Negeri Lampung, 2018)
The purpose of this research was to determine the factors that influence the level of sales â€œtokokelontongâ€ on Sukarame Bandar Lampung. Methods of data collection was done by a list ofquestions (questionnaire), interviews, observation, documentation. And using a samplingtechnique that uses accidental sampling technique for sampling in 40 respondence. the resultsshowed factors affecting sales are price factor, product quality, competition.